DAYA TARIK PACU JAWI SEBAGAI ATRAKSI WISATA BUDAYA DI KABUPATEN TANAH DATAR - Purnama Suzanti (JURNAL NASIONAL PARIWISATA, 2014)
Pacu Jawi (cow racing) is traditional attraction which is village children (games entertain and convey the noble values by the village children) after rice harvest, in the form of a pair of cows in the fields spur watery and muddy. This activity has become a community tradition that survives in four districts namely Sungai Tarab sub district, Pariangan, Five People, and propagation in Tanah Datar. This tradition since 2009 won several photo contests nationally and internationally so that tourists. The study aims to explain the essence of tourist attraction Pacu Jawi. The method used is qualitative research methodology. Data was collected with a literature study, observation and interviews. Studies conducted with collecting information relating to tourist attraction and Runway Jawi. Interview done face to face, telephone, and social media networking internet (chat). The results show the attractiveness Pacu Jawi is the passion and spirit of excitement that looks at the jockey, the owner of the cow, the public, government and tourists. Panorama of nature, the spirit of excitement to attract Pacu Jawi in photography. Pacu Jawi uniqueness lies in the location of implementation, in the form of rice field terraces, muddy and watery. Pacu Jawi implemented to move from one village to another village.